A retrospective analysis of semen parameters among males at an infertility clinic in Nairobi, Kenya (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Male infertility affects a significant proportion of couples trying to conceive because of a variety of factors, such as low sperm count, abnormal sperm morphology, erectile dysfunction, varicocele, infections, and hormonal imbalances. This study aimed to assess the prevalence of male infertility in Nairobi, Kenya, and to better understand the causes of male infertility and improve outcomes for couples struggling to conceive.Methods: A retrospective study was conducted at an infertility clinic in Nairobi, Kenya between February 2021 and September 2022. 115 men who underwent semen analysis were chosen. Descriptive statistics were calculated for demographics and sperm parameters using SPSS version 27. Results: The average age range of study participants was 21-56 years.  In most cases, 63% had progressive sperm motility, 28.3% had nonprogressive motility, and 8.7% had sperm immotility. A sperm concentration of